METODOLOGIA PARA O DIAGNÓSTICO DE FONTES FIXAS DE EMISSÃO ATMOSFÉRICA POR MEIO DE UM VANT DE BAIXO CUSTO - Ferraz, Patrícia Fontes (2021)
Air pollution is a topic of relevant interest as it directly affects the health and well-being of the population. Its study is complex because it is a heterogeneous mixture, the result of different emission sources, with a different composition. One of the main sources of atmospheric pollution emissions are stationary or fixed, such as industrial ducts and stacks, which must be adequately dimensioned, considering factors such as the topography and buildings neighboring the point sources, so that the emission of pollutants reaches the receivers (neighboring population) in a sufficiently diluted manner so as not to cause any harmful effect to it. In this sense, geoprocessing and remote sensing are an alternative for managing air quality control, with UAVs standing out as a practical and low-cost tool for obtaining information such as land use and occupation characteristics, topography and even information about the dimensions of the imaged objects. Given the above, the present research aimed to evaluate the sources of punctual atmospheric emissions that use wood and its derivatives as fuel, located in the urban perimeter of Irati / PR, in order to verify the dispersion of its pollutants. The research was divided into phases, which are the definition of fixed point sources; flight planning; conducting aerial surveys; image processing, generation of models and orthomosaics; the validation of the measures; the implementation of data in a GIS environment; and environmental analysis of the studied areas according to the environmental legislation and theoretical framework. Statistical analysis was also carried out on the data from the heights of the buildings, with a comparison between the data obtained in the field and those obtained from the models (MDS and MDT). The use of UAVs proved to be viable for determining the height of buildings inserted in the areas of influence of sources of atmospheric emission. The data validation performed showed the following errors in the estimate: RMSE = 20 cm and R-RMSE = 4.93%, resulting in R2 of 0.99. However, for the identification of the stacks and determination of their dimensions, further studies are needed, changing the flight planning to solve the problems of radial distortion and occlusions observed in the orthomatics.